THE INFLUENCE OF HUMAN RESOURCE COMPETENCE, IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS AND REGIONAL FINANCIAL ACCOUNTING SYSTEMS ON THE QUALITY OF REGIONAL FINANCIAL REPORTS (EMPIRICAL STUDY OF SKPD SUKOHARJO REGENCY) - Aprilia Siti Rahayu; Suhesti Ningsih; Desy Nur Pratiwi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract This research aims to determine the effect of the competence of human resources, the application of government accounting standards, and the regional financial accounting system on the quality of local government financial reports at the SKPD of Sukoharjo Regency. This type of research is quantitative research with a survey approach using an instrument in the form of a closed questionnaire with a Likert scale. The sample in this research were employees who worked in the finance or budget or treasury department at SKPD Sukoharjo who met the criteria for the research sample as many as 66 people. The data analysis method used multiple linear regression analysis with the help of SPSS 25.0 program. The results of the analysis show that the competence of human resources, the application of government accounting standards, and the regional financial accounting system have a significant positive effect on the quality of local government financial reports at the SKPD of Sukoharjo Regency either simultaneously or partially. The results of the analysis of the coefficient of determination obtained a value of 63.8% of human resource competence, the application of government accounting standards, and the regional financial accounting system was able to explain the variation of changes in the quality of local government financial report variables and the remaining 36.2% was explained by other variables outside the model. this research. Keywords: Competence of Human Resources, Application of Government Aaccounting Standards, Regional Financial Accounting Systems, Quality of Local Government Financial Reports